2017
DOI: 10.4025/actasciagron.v39i3.32700
|View full text |Cite
|
Sign up to set email alerts
|

<b>Developing an <i>in vitro</i> optimized protocol to sweet potato landraces conservation

Abstract: This study aimed to develop a protocol for the in vitro conservation of 30 accessions of sweet potato collected in the northern region of Rio de Janeiro State, Brazil, aiming to extend the period between subcultures for this species. An in vitro minimal growth experiment was established with accession UENF 1931 in a factorial arrangement consisting of four concentrations of mineral salts in MS medium and four concentrations of sucrose, at two temperatures. The others accessions were grown in medium containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…For example, nodal explants were used for the micropropagation of 'Carmen Rubin' and 'White Triumph' (Dolinski and Olek, 2013), 'Gaozi No. 1' (Gong et al, 2005), 'Naruto Kintoki' (Teixeira da Silva et al, 2007), 'KSP 36' and 'KEMB 36' (Mvuria and Ombori, 2014), and 30 accessions from the northern region of Rio de Janeiro, Brazil (Vettorazzi et al, 2017). However, little is known about the micropropagation of 'Abees' sweet potato.…”
Section: Introductionmentioning
confidence: 99%
“…For example, nodal explants were used for the micropropagation of 'Carmen Rubin' and 'White Triumph' (Dolinski and Olek, 2013), 'Gaozi No. 1' (Gong et al, 2005), 'Naruto Kintoki' (Teixeira da Silva et al, 2007), 'KSP 36' and 'KEMB 36' (Mvuria and Ombori, 2014), and 30 accessions from the northern region of Rio de Janeiro, Brazil (Vettorazzi et al, 2017). However, little is known about the micropropagation of 'Abees' sweet potato.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary study carried out indicated that calli induction on modified MS medium containing 2, 4-D on similar explants as reported by [3] under the culture conditions was difficult, if not impossible, with the PNG cultivars tested. In addition, [6] reported that embryogenic calli was induced on LS-based medium supplemented with 1 mgL -1 picloram and more than 50% of the embryogenic calli of 11 genotypes cultured produced shoots.…”
Section: Induction Of Embryogenic Callusmentioning
confidence: 55%
“…Reports of similar research by others [3,6,10] showed that sweet potato is recalcitrant to every in vitro culture treatment and occur at low frequencies for various explants. In fact, shoots can easily be regenerated from explants of stems, petioles, leaves and roots but callus induction and shoot regeneration is difficult, if not impossible [11].…”
Section: Plantlet Regeneration Potential Of Callimentioning
confidence: 91%
See 2 more Smart Citations